Ethical Reasoning in Accounting and Auditing. - Boatsman, James R.; Shaub, Michael K. (The Accounting Review, 1995)
Abstract Reviews the book `Ethical Reasoning in Accounting and Auditing,' by Lawrence A. Ponemon and David R.L. Gabhart.